1961
DOI: 10.1017/s0021859600049807
|View full text |Cite
|
Sign up to set email alerts
|

The grazing behaviour and free-water intake of East African shorthorned zebu heifers at Serere, Uganda

Abstract: 1. Results are presented which refer to the behaviour of twenty young East African shorthorned zebu heifers grazing a Chloris gayana ley at Serere Experiment Station in north-east Uganda. The heifers were studied for two trial periods, each of 72 hr. duration, one during the transitional season and one during the dry season.2. Five of the heifers were recorded individually, and the results showed a fair degree of variation in behaviour between heifers. The difference in total ruminating time between two heifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
1

Year Published

1965
1965
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 14 publications
1
3
0
1
Order By: Relevance
“…in the dry season of malnutrition (Smith, 1959). Approximately 20% of this grazing was done at night, which agrees with observations made in Ghana (Rose-Innes, 1963), Uganda (Wilson, 1961), and Tanganyika (Lampkin & Quarterman, 1962), but is higher than found in Uganda (Harker, Taylor 6 Rollinson, 1956) and previously in Tanganyika (Lampkin & Quarterman, 1958).…”
supporting
confidence: 86%
See 1 more Smart Citation
“…in the dry season of malnutrition (Smith, 1959). Approximately 20% of this grazing was done at night, which agrees with observations made in Ghana (Rose-Innes, 1963), Uganda (Wilson, 1961), and Tanganyika (Lampkin & Quarterman, 1962), but is higher than found in Uganda (Harker, Taylor 6 Rollinson, 1956) and previously in Tanganyika (Lampkin & Quarterman, 1958).…”
supporting
confidence: 86%
“…grazing day reduced cattle growth during the dry season when the veld is deficient in quality, or when a quantitative feed deficiency occurs due to over stocking during the rains. Wilson (1961) gives the only data on African -* Present address: C.S.I.R.O., Lawes, Queensland, Australia. owned cattle, the results being confined to one herd near Serere, Uganda.…”
mentioning
confidence: 99%
“…Night observations were made only in moonlight. Wilson (1961) found that moonlight did not alter the nocturnal activity of cattle. On occasions, various aspects of rumination were measured in detail in animals of all ages both in and out of the herd.…”
Section: Feeding Behaviourmentioning
confidence: 90%
“…Smith (1959) and Wilson (1961) reported that nightgrazing by African zebu breeds kept in paddocks could occupy up to 4 h of the nighttime activity, particularly during the dry season when forage was in short supply. However, this was atypical and 2 h per night was more normal.…”
Section: Foraging Behaviour Factorsmentioning
confidence: 99%